Edukasi interaktif dalam penerapan cuci tangan pakai sabun pada anak usia dini - Widadi, Sri Yekti; Rissaadah, Siti; Pebriani, Aulia (JOURNAL of Public Health Concerns, 2026)
Background: Early childhood is at high risk of infectious diseases due to an immature immune system and inadequate hand hygiene habits. Handwashing with soap is a simple yet effective disease prevention practice that needs to be instilled early. Purpose: To improve early childhood knowledge and skills in implementing clean and healthy handwashing behaviors. Method: This community service activity was conducted at PGTK Pelita Hati in December 2025, targeting early childhood children (4-7 years old) currently studying at PGTK Pelita Hati. Eighty-one PGTK Pelita Hati students participated in the activity. The intervention included health education about handwashing with soap through demonstrations and educational games tailored to the developmental stages of early childhood. To increase children's understanding and enthusiasm, the activity also combined singing and interactive question-and-answer sessions. An observational assessment questionnaire was used to measure participants' knowledge and understanding throughout the activity. Observations were conducted before and after the educational activity (pre-test) and after the educational activity (post-test). As an evaluation of activities by comparing the assessment results before educational activities (pre-test) with after educational activities (post-test). Results: showed an increase in children's knowledge, skills, and participation in the good category after the educational intervention. Before the activity, only 24 children (29.6%) understood the meaning of handwashing with soap and 21 children (25.9%) knew the benefits of handwashing with soap. After the activity, this number increased to 70 children (86.4%) who understood the meaning of handwashing with soap and 68 children (84.0%) who knew the benefits of handwashing with soap. Children's knowledge about important times to wash their hands also increased, from 19 children (23.5%) before the activity to 66 children (81.5%) after the activity. In terms of skills, before the activity, only 17 children (21.0%) were able to practice the six steps of handwashing with soap correctly. After education through demonstrations and direct practice, the number of children who were able to practice the six steps of handwashing with soap increased to 65 children (80.2%). In addition, children's activeness and participation during the activity also showed an increase, from 34 children (42.0%) before the activity to 74 children (91.4%) after the activity. Conclusion: Community service activities in the form of health education on handwashing with soap for early childhood, using a demonstrative, participatory educational approach, combined with play and singing, were highly effective in improving children's understanding of the meaning and benefits of handwashing with soap, recognizing important handwashing times, and correctly practicing the six steps of handwashing with soap. Furthermore, the involvement of teachers and facilitators provided crucial support in reinforcing health messages and sustaining handwashing with soap behavior in the school environment. Suggestion: School-based handwashing with soap health education is expected to continue to be developed, as it has significant potential as a promotional and preventive measure in preventing infectious diseases and fostering clean and healthy living habits from an early age. Keywords: Community service; Early childhood; Health education; Handwashing with soap Pendahuluan: Anak usia dini memiliki risiko tinggi terhadap penyakit infeksi akibat sistem imun yang belum matang dan kebiasaan kebersihan tangan yang belum terbentuk secara optimal. Cuci Tangan Pakai Sabun (CTPS) merupakan perilaku sederhana namun efektif dalam pencegahan penyakit yang perlu ditanamkan sejak dini. Tujuan: Untuk meningkatkan pengetahuan dan keterampilan anak usia dini dalam menerapkan perilaku bersih dan sehat dengan cuci tangan pakai sabun. Metode: Kegiatan pengabdian masyarakat ini dilaksanakan di PGTK Pelita Hati pada bulan Desember 2025 dengan sasaran anak usia dini (4-7 tahun) yang sedang menempuh pendidikan di PGTK Pelita Hati. Kegiatan ini melibatkan 81 siswa/siswi PGTK Pelita Hati untuk menjadi partisipan. Intervensi berupa pendidikan kesehatan tentang cuci tangan pakai sabun (CTPS) melalui pendekatan demonstrasi dan permainan edukatif yang disesuaikan dengan tahap perkembangan anak usia dini. Untuk meningkatkan pemahaman dan antusiasme anak, kegiatan juga dikombinasikan dengan metode bernyanyi dan tanya-jawab interaktif. Menggunakan kuesioner penilaian observasi untuk mengukur tingkat pengetahuan dan pemahaman partisipan selama proses kegiatan. Observasi dilakukan sebelum kegiatan edukasi (pre-test) dan setelah kegiatan edukasi (post-test). Sebagai evaluasi kegiatan dengan membandingkan hasil penilaian sebelum kegiatan edukasi (pre-test) dengan sesudah kegiatan edukasi (post-test). Hasil: menunjukkan terdapat peningkatan pengetahuan, keterampilan, dan partisipasi anak yang dalam kategori baik setelah dilakukan intervensi edukasi. Sebelum kegiatan, hanya 24 anak (29.6%) yang memahami pengertian CTPS dan 21 anak (25.9%) yang mengetahui manfaat CTPS. Setelah kegiatan, jumlah tersebut meningkat menjadi 70 anak (86.4%) yang memahami pengertian CTPS dan 68 anak (84.0%) yang mengetahui manfaat CTPS. Pengetahuan anak mengenai waktu-waktu penting mencuci tangan juga mengalami peningkatan, dari 19 anak (23.5%) sebelum kegiatan menjadi 66 anak (81.5%) setelah kegiatan. Pada aspek keterampilan, sebelum kegiatan hanya 17 anak (21.0%) yang mampu mempraktikkan enam langkah CTPS dengan benar. Setelah dilakukan edukasi melalui demonstrasi dan praktik langsung, jumlah anak yang mampu mempraktikkan enam langkah CTPS meningkat menjadi 65 anak (80.2%). Selain itu, keaktifan dan partisipasi anak selama kegiatan juga menunjukkan peningkatan, dari 34 anak (42.0%) sebelum kegiatan menjadi 74 anak (91.4%) setelah kegiatan. Simpulan: Kegiatan pengabdian masyarakat berupa pendidikan kesehatan tentang cuci tangan pakai sabun (CTPS) pada anak usia dini melalui pendekatan edukasi yang bersifat demonstratif, partisipatif, serta dikombinasikan dengan metode bermain dan bernyanyi sangat efektif meningkatkan kemampuan anak dalam memahami pengertian dan manfaat CTPS, mengenali waktu-waktu penting mencuci tangan, serta mempraktikkan enam langkah CTPS dengan benar. Selain itu, keterlibatan guru dan fasilitator memberikan dukungan penting dalam memperkuat pesan kesehatan dan keberlanjutan perilaku CTPS di lingkungan sekolah. Saran: Diharapkan, pendidikan kesehatan CTPS berbasis sekolah untuk terus dikembangkan karena memiliki potensi besar sebagai upaya promotif dan preventif dalam mencegah penyakit infeksi serta membentuk kebiasaan hidup bersih dan sehat sejak usia dini.